2021
DOI: 10.1016/j.apsb.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Identifying potential anti-COVID-19 pharmacological components of traditional Chinese medicine Lianhuaqingwen capsule based on human exposure and ACE2 biochromatography screening

Abstract: Lianhuaqingwen (LHQW) capsule, a herb medicine product, has been clinically proved to be effective in coronavirus disease 2019 (COVID-19) pneumonia treatment. However, human exposure to LHQW components and their pharmacological effects remain largely unknown. Hence, this study aimed to determine human exposure to LHQW components and their anti-COVID-19 pharmacological activities. Analysis of LHQW component profiles in human plasma and urine after repeated therapeutic dosing was conducted using a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 41 publications
3
115
0
1
Order By: Relevance
“…In the present study, the ACE2/CMC model was combined with HPLC-IT-TOF-MS to develop a two-dimensional analysis method for TCMs screening, making the screening work more efficient, fast, and convenient. Chen et al [ 40 ] also synthesized a novel ACE2 biochromatographic stationary phase for the screening of potential ACE2-targeted components from extract of Lianhuaqingwen capsule. Results confirmed the suitability and efficiency of ACE2/CMC model and its coupled system.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the ACE2/CMC model was combined with HPLC-IT-TOF-MS to develop a two-dimensional analysis method for TCMs screening, making the screening work more efficient, fast, and convenient. Chen et al [ 40 ] also synthesized a novel ACE2 biochromatographic stationary phase for the screening of potential ACE2-targeted components from extract of Lianhuaqingwen capsule. Results confirmed the suitability and efficiency of ACE2/CMC model and its coupled system.…”
Section: Resultsmentioning
confidence: 99%
“…LHQW could reduce patient mortality, improve clinical symptoms (such as fever, cough, fatigue) for COVID-19. [ 11 ] The results network pharmacology showed that LHQW prescription acted on coronavirus through multiple components, multiple targets, and multiple pathways. The major components not only have good binding ability with ACE2, but also effectively bind to the contact surface of ACE2 and the spinous process complex, thus playing a potential therapeutic role in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…(B) Raw materials of Lianhuaqingwen capsules. (C) Molecular docking of representative components (prunasin, rhein, forsythoside I, and neochlorogenic acid) with ACE2 (image reproduced with permission from Chen et al, 2020c ). …”
Section: Promising Chinese Herbal Medicine Formulas For the Treatmentmentioning
confidence: 99%
“…Results demonstrated that certain representative components exhibited high inhibitory effects on ACE2, including prunasin (affects the binding interface of ACE2 and S protein), rhein (the best binding interface of ACE2), forsythoside I (the binding interface of ACE2), and neochlorogenic acid (the binding interface of peptidase and S protein) ( Fig. 8 C) ( Chen et al, 2020c ). As a large formulation, LHQW may possess complex mechanisms of action; however, these are currently undefined and require additional research.…”
Section: Promising Chinese Herbal Medicine Formulas For the Treatmentmentioning
confidence: 99%